The Design of Ichsan Sidenreng Rappang University Using a Neo-Vernacular Architectural Approach - Zulkifli Mangaru; Nurhayati Kamaruddin; Izharul Haq (Universitas Ichsan Sidenreng Rappang, 2026)
Sidenreng Rappang Regency experiences limited access to higher education due to a shortage of adequate facilities. One of the local higher education institutions, Ichsan University of Sidenreng Rappang, currently operates in the former regency office under a non-permanent lease contract. This conversion of office space into an educational facility triggers a crisis of physical identity, restricts academic development, and disrupts the comfort and efficiency of the academic community. This descriptive qualitative study proposes the design of a new campus for Ichsan University by applying a Neo-Vernacular Architecture approach. Primary data were collected through field observations, site surveys, and interviews with the university management and community figures. These data were integrated with secondary data comprising regulatory studies and Bugis local wisdom literature, which were subsequently processed through data reduction and triangulation stages. The study produces a comprehensive campus design framework that integrates traditional Bugis cultural values. The transformation of local elements is realized modernly through the adaptation of the three-layer macrocosm concept (Rakkeang, Watang Pola, Awa Bola) into building mass zoning, the implementation of the Sulapa Appa philosophy into spatial geometry, a climate-based mass orientation (bola mabbuju), and the stylization of traditional local decorative arts on contemporary facade details. It can be concluded that the application of Neo-Vernacular Architecture successfully aligns the identity of local wisdom with current higher education facilities. This design not only provides a versatile and sustainable venue for Tridharma (the Three Pillars of Higher Education) activities but also serves as an architectural realization that reinforces institutional identity and the pride of the Sidenreng Rappang community.